Autogenous Bone Reconstruction of Large Secondary Skull Defects. Issue 2 (February 2017) - Fearon, Jeffrey A.; Griner, Devan; Ditthakasem, Kanlaya; Herbert, Morley
Abstract : Background: The authors sought to ascertain the upper limits of secondary skull defect size amenable to autogenous reconstructions and to examine outcomes of a surgical series. Published data for autogenous and alloplastic skull reconstructions were also examined to explore associations that might guide treatment. Methods: A retrospective review of autogenously reconstructed secondary skull defects was undertaken. A structured literature review was also performed to assess potential differences in reported outcomes between autogenous bone and synthetic alloplastic skull reconstructions. Weighted risks were calculated for statistical testing. Results: Ninety-six patients underwent autogenous skull reconstruction for an average defect size of 93 cm 2 (range, 4 to 506 cm 2 ) at a mean age of 12.9 years. The mean operative time was 3.4 hours, 2 percent required allogeneic blood transfusions, and the average length of stay was less than 3 days. The mean length of follow-up was 28 months. There were no postoperative infections requiring surgery, but one patient underwent secondary grafting for partial bone resorption. An analysis of 34 studies revealed that complications, infections, and reoperations were more commonly reported with alloplastic than with autogenous reconstructions (relative risk, 1.57, 4.8, and 1.48, respectively). Conclusions: Autogenous reconstructions are feasible, with minimal associated morbidity, for patients with skull defect sizes as large as 500 cm 2 . A structured literature review suggests that autogenous bone reconstructions are associated with lower reported infection, complication, and reoperation rates compared with synthetic alloplasts. Based on these findings, surgeons might consider using autogenous reconstructions even for larger skull defects. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.